Propafenone effect on inotropic myocardial function in patients with recurrent atral fibrillation - I. G. Fomina; A. I. Tarzimanova; A. V. Vetluzhsky (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of three-month propafenone antiarrhythmic therapy (daily dose 450 mg) on inotropic myocardial function in patients with recurrent atrial fibrillation (AF). Material and methods. The study included 18 (100%) patients aged 39-59 years (mean age 51.7±6.7 years), receiving propafenone (450 mg/d) for 3 months, to prevent recurrent AF. To assess antiarrhythmic therapy effects on inotropic myocardial function, all participants underwent balanced radionuclide ventriculography at baseline; in patients with maintained sinus rhythm, it was repeated after 3 months of treatment. Results. In first 3 days after restoring sinus rhythm in recurrent AF patients, diastolic function dynamics was observed: significant reduction in 1/3 diastole filling and peak filling velocity. After 3 months of propafenone treatment, left ventricular (LF) 1/3 diastole filling (p<0.05), as well as LV and right ventricular (RV) filling peak velocity (p<0.05), significantly increased. Ejection fraction, systolic and volumic parameters of LV and RV stayed within the normal range and did not change significantly. After 3-month propafenone therapy, recurrent AF patients demonstrated significant increase in atrial input into LV diastole – from 17.1±5.7% to 22.1±6.5%, and RV diastole – from 17.3±5.1% to 21.1±6.2% (р<0.05). Conclusion. Propafenone therapy (450 mg/d) facilitated 3-month sinus rhythm maintenance in 77% patients with recurrent AF. The therapy did not affect LF and RV inotropic myocardial function. Maintaining sinus rhythm for 3 moths facilitated normalization of atrial contractility and ventricular diastolic dysfunction improvement.